2007
DOI: 10.1111/j.1365-2958.2007.05860.x
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of the RpoS regulon in Borrelia burgdorferi in response to mammalian host signals provides insight into RpoS function during the enzootic cycle

Abstract: Summary Borrelia burgdorferi (Bb) adapts to its arthropod and mammalian hosts by altering its transcriptional and antigenic profiles in response to

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

35
504
1

Year Published

2008
2008
2017
2017

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 243 publications
(540 citation statements)
references
References 125 publications
35
504
1
Order By: Relevance
“…77, 2009 CsrA OF B. BURGDORFERI 5159 following a blood meal (51,52). The significant increase in the levels of BBA64 upon overexpression of CsrA Bb independent of the environmental signals like pH or temperature is indicative of a distinct role for CsrA Bb , as BBA64 has been previously shown to be regulated by the RpoN/RpoS-dependent signaling network (20). It will be interesting to determine if the levels of BBA64 are coregulated by both CsrA and RpoN/ RpoS in response to various environmental signals.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…77, 2009 CsrA OF B. BURGDORFERI 5159 following a blood meal (51,52). The significant increase in the levels of BBA64 upon overexpression of CsrA Bb independent of the environmental signals like pH or temperature is indicative of a distinct role for CsrA Bb , as BBA64 has been previously shown to be regulated by the RpoN/RpoS-dependent signaling network (20). It will be interesting to determine if the levels of BBA64 are coregulated by both CsrA and RpoN/ RpoS in response to various environmental signals.…”
Section: Discussionmentioning
confidence: 98%
“…In addition, the genome of B. burgdorferi codes for a limited number of regulators to control myriad metabolic processes, leading to overlapping or discrete networks responding to different environmental signals (32). Currently, much of the information on gene regulation in B. burgdorferi has been obtained from the analysis of a central regulatory pathway mediated by Rrp2-RpoN-RpoS (17,20,31,41,86). The activation of this pathway facilitates a concerted expression of a variety of borrelial determinants, such as OspC, DbpA/B, and BBK32, known to be involved in the pathogenic mechanisms of B. burgdorferi (41,86).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, all of the motility promoters identified so far are 70 -like (19,22,38). However, discrimination between S and 70 promoters in B. burgdorferi based on promoter consensus sequences is problematic (11,66). Recently, using microarray and transcriptional analysis, Caimano et al have shown that whereas flagellum biosynthetic genes are controlled by 70 both in vitro and in vivo, the methyl-accepting chemotaxis genes mcp1, mcp4, and mcp5 and the chemotaxis gene cheW2 are upregulated by S (RpoS) (11) during growth in vivo.…”
Section: Discussionmentioning
confidence: 99%
“…A sensor-regulator pair of proteins also contributes to this regulation [154]. When B. burgdorferi mutants were tested in the infection model, rpoS and rpoN expression were found to be required for infecting mice [153,155], demonstrating the importance of this pathway for survival in a mammal.…”
Section: B Burgdorferi Products Required For Mammalian Infectionmentioning
confidence: 99%